Li/graphene oxide primary battery system and mechanism. Issue 2 (27th January 2022) - Kornilov, Denis; Penki, Tirupathi Rao; Cheglakov, Andrey; Aurbach, Doron
Abstract: A novel type of Li/graphene oxide (Li/GO) battery based on a spontaneous redox reaction between Li metal and GO cathode is introduced as an alternative viable primary battery system. Here, we present an efficient synthesis of GO by the modified Hummers method and focus on a comprehensive study of the reduction mechanism. The Li/GO battery was thoroughly analyzed by various physical and electrochemical methods. GO rich in oxygen‐bearing functional groups on graphene layers provided lithium storage sites and delivered a high discharge capacity of around 720 mAh/g at 12 mA/g. Products formed on the surface during reduction were analyzed, and a mechanism was proposed. The results uncovered the reasons underlying the improved electrochemical properties and the contribution of the irreversible capacity of reduced GO in graphene‐based composite electrode materials for metal‐ion batteries. The Li/GO concept is expected to shed light on the design of similar M/GO batteries based on other active metal anodes (e.g., M = Na, Mg, Al, Zn). Abstract : Graphene‐oxide synthesis and Li/GO cell production.